FARMERS HOUSEHOLD’S FOOD SECURITY IN THE DISTRICT OF PONJONG, GUNUNGKIDUL REGENCY - Radita Dwi Rahmi; Ken Suratiyah; Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2013)
The aims of this research are (1) to find out farmers household’s food expenditure (2) to analyze the food security level of farmers household (3) to know they factors that influence the food security of farmers household. The basic method of this research is descriptive analysis. The respondents were determined purposively, there were 30 respomdents who came from farmer family having rice farming, corn farming, soybean farming, cassava farming, and peanuts farming in Ponjong Sub District. Analysis of the data was conducted by determining the level of food security viewed from the share of food expenditure, the method of Johnson and Toole, the indicators of food security index ad the food insecurity. Whereas, Ordinat Least Sugar method was carried out to determine the factors that influence farmers household’s food. The result show that (1) the average of farmers household’s food expenditure are about Rp 13.090.728, with the average share of food expenditure by 65,20% (2) the level of farmers households food security is observed by the food security index indicator are classified as food secure, and do not have experience in food insecurity. While it is according ro Johnson and Toole’s method the farmers households’ are classified as food insecure (3) income households can increase food security, while the family size, cooking oil price, and tempe price are likely to reduce the level of farmers household’s food security the Ponjong district.